Cycad Aulacaspis Scale, a Newly Introduced Insect Pest in Indonesia - RANGASWAMY MUNIAPPAN; GILLIAN W. WATSON; GREGORY ALLYN EVANS; AUNU RAUF; NATALIA VON ELLENRIEDER (Bogor Agricultural University, Indonesia, 2012)
Cycad aulacaspis scale (Aulacaspis yasumatsui Takagi (Hemiptera: Diaspididae)) is native to Thailand and Vietnam. Since the early 1990s it has been spreading around the world due to the trade in cycad plants for ornamental use. Infestation by this scale can kill cycads in only a few months. Its accidental introduction to Florida endangered the ornamental cycad-growing industry; and in Guam and Taiwan, endemic cycads (Cycas micronesica and C. taitungensis, respectively) are currently threatened with extinction by cycad aulacaspis scale. In November 2011, an introduced scale was discovered damaging cycads in the Bogor Botanic Garden. Samples from Bogor were taken for identification of the scale, and the material was kept for some time to rear out any insect parasitoids that were present. Both the scale insects and parasitoids were prepared on microscope slides and studied microscopically for authoritative identification. The scale was confirmed as A. yasumatsui. The parasitoid Arrhenophagus chionaspidis Aurivillius (Hymenoptera: Encyrtidae) and the hyperparasitoid Signiphora bifasciata Ashmead (Hymenoptera: Signiphoridae) were identified from the samples. Unless immediate remedial measures are taken, several endemic species of cycad in Indonesia may be endangered by infestation by cycad aulacaspis scale.